-9+k+3k=9-2k

Simple and best practice solution for -9+k+3k=9-2k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9+k+3k=9-2k equation:


Simplifying
-9 + k + 3k = 9 + -2k

Combine like terms: k + 3k = 4k
-9 + 4k = 9 + -2k

Solving
-9 + 4k = 9 + -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
-9 + 4k + 2k = 9 + -2k + 2k

Combine like terms: 4k + 2k = 6k
-9 + 6k = 9 + -2k + 2k

Combine like terms: -2k + 2k = 0
-9 + 6k = 9 + 0
-9 + 6k = 9

Add '9' to each side of the equation.
-9 + 9 + 6k = 9 + 9

Combine like terms: -9 + 9 = 0
0 + 6k = 9 + 9
6k = 9 + 9

Combine like terms: 9 + 9 = 18
6k = 18

Divide each side by '6'.
k = 3

Simplifying
k = 3

See similar equations:

| 14x-21=12x+29 | | 3x+2(x+10)=170 | | N*(2n-4)=17 | | 28x+52=25 | | 3x^2+2x^2=0 | | 2(v+8)=8(-v-8) | | 5+7x=96 | | 7a+2=1 | | 1.5-.4y=3.3 | | 6x^2-44x=-63 | | -(7v+7)=5-4v | | Q+83=902 | | p=6+7p | | -38=2(-43d-24) | | 9c-6-6c=16 | | 4(y+1)=6y-8 | | -10-3h=8h+3+9 | | (4m-120)= | | -8(r-6)=-8-6(-2+5r) | | -13m+7m=18-66 | | 8.7x=156.6 | | 5x-(3x-2)=18 | | -8x-8=3x+25 | | -8-5(1+6x)=5(1-6x)2x | | -3+a/4=-4 | | V+4-8=6(v+7)+2(v+5) | | 8(x-7)=-112 | | -12-11d=-10d | | ax+bx=-4 | | X=10x-78 | | 3x+4x=6x-8 | | 2x+5+2x-23=90 |

Equations solver categories